2022
DOI: 10.33824/pjpr.2022.37.4.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mood and School Related Stress on Academic Performance: A Mood Induction Investigation

Abstract: This experimental research has been designed to explore the impact of visual cues (visual clips) of school stress on student’s mood and academic performance. It was aimed at investigating the relation between positive guided imagery and negative mood. Participants in the study included 90 boys and 95 girls (N = 185) with the age range of 10-14 years. The sample was randomly selected from different public and private schools of Multan and Bahawalpur. They were randomly assigned to two groups: Group 1 had negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Based on the regression equation model obtained in this study shows that emotional intelligence is higher than self-efficacy in lowering academic procrastination attitudes. This is in accordance with the results of the study (Aziz and Batool 2022). The results of subsequent studies showed that together emotional intelligence and self-efficacy can predict academic procrastination.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the regression equation model obtained in this study shows that emotional intelligence is higher than self-efficacy in lowering academic procrastination attitudes. This is in accordance with the results of the study (Aziz and Batool 2022). The results of subsequent studies showed that together emotional intelligence and self-efficacy can predict academic procrastination.…”
Section: Discussionsupporting
confidence: 92%